2007
DOI: 10.1021/ie0703639
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Boron Removal by Mg/Al Double-Layered Hydroxides

Abstract: This paper is concerned with the preparation and use of Mg/Al double-layered hydroxides for boron removal from waste liquor. The structure of the DLHs synthesized is proposed to be Mg 2 AlNa 1.4 (OH) 7.57 Cl 0.03 (NO 3 ) 0.8 ‚ x(H 2 O) which does not contain any carbonate anions. For treating model waters with various starting boron concentrations (5-500 mg/L), the maximum boron percentage removal was >80% for DLH-60 and >90% for DLH-450. The boron removal capacity is 5.4-17.3 mg of B/g for DLH-450 and 1.2-13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…Preparatics of original DLH substance, prepared using magnesium nitrate(V), aluminium chloride and sodium hydroxide, is described in detail in literature [19]. Detailed research performed with the preparation mentioned above led to some appropriate modifications of original DLH preparation, and in consequence obtaining stable preparation, efficiently removing boron and avoiding significant saltness of solution, denoted as DLH/NO3-Cl/M in subsequent text [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparatics of original DLH substance, prepared using magnesium nitrate(V), aluminium chloride and sodium hydroxide, is described in detail in literature [19]. Detailed research performed with the preparation mentioned above led to some appropriate modifications of original DLH preparation, and in consequence obtaining stable preparation, efficiently removing boron and avoiding significant saltness of solution, denoted as DLH/NO3-Cl/M in subsequent text [24].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous difficulties and economical disadvantages of processes mentioned above were the impulse for new research works oriented on establishing effective and economically reasonable methods of boron removal, since according to the World Health Organization [18], boron is an element that cannot be removed using conventional methods of water and wastewater processing. One of recently tested technologies of boron removal are doublelayered hydroxides [19]. Double-layered hydroxides (DLH) are a kind of synthetic silty materials with a structure described by the formula M(II)1-xM(III)x(OH)2(A n-)x/n•mH2O, where both bivalent M(II) and trivalent M(III) cations form positively charged layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder XRD showed that the interlayer space increased from 3.8 to 4.8Å to accommodate borate ions indicating that the mechanism of boron uptake for the uncalcined LDH was anion exchange [3]. Jiang et al [55] investigated the removal of boron from aqueous solutions using Mg/Al Finally, the possibility of regenerating the LDH sorbents was investigated. A 5M solution of sodium nitrate (NaNO 3 ) was chosen for regenerating the LDHs as it was expected to result in the highest boron uptake capacity.…”
Section: Mg/al Hydrotalcite Like Ldhs For the Removal Of Boron From Smentioning
confidence: 99%
“…Boron removal decreased with the increasing number of regenerations with the Mg/Al LDH still removing 69% of boron present. The thermally activated LDH removed only around 54% of boron present after three regenerations indicating that a significant decomposition of the adsorbent must have occurred during the repeated regeneration cycles [55]. and aluminium nitrate (2.93g) into a fine paste.…”
Section: Mg/al Hydrotalcite Like Ldhs For the Removal Of Boron From Smentioning
confidence: 99%